Asuhan Keperawatan Medikal Bedah pada Pasien dengan Penyakit Paru Obtruktif Kronik (PPOK) di Ruangan Paru Rumah Sakit Prof. H. M. Yamin, S. H Pariaman - Cantika Mulya; Hilma Yessi S; Debby Silvia Dewi; Mike Asmaria (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a major health problem characterized by progressive and not fully reversible airflow limitation, which significantly affects patients’ quality of life, particularly due to ineffective breathing patterns. Based on literature review, COPD is associated with risk factors such as smoking habits, air pollution exposure, and a history of chronic respiratory diseases, with nursing theories emphasizing the fulfillment of oxygenation needs and the effectiveness of breathing patterns. This study used a descriptive method with a case study approach aimed at identifying nursing problems and providing appropriate interventions in COPD patients. Data were collected through interviews, observations, physical examinations, and documentation studies, then analyzed by comparing findings with relevant theories. The results showed that the patient experienced an ineffective breathing pattern characterized by shortness of breath, use of accessory respiratory muscles, and decreased oxygen saturation. Nursing interventions included breathing exercises, semi-Fowler positioning, and health education. Evaluation indicated an improvement in the patient’s condition, marked by reduced dyspnea and improved breathing pattern effectiveness. The conclusion of this study is that appropriate, systematic, and continuous nursing care can improve breathing pattern effectiveness in COPD patients and support optimal recovery.